High Torque Flux Switching Permanent Magnet Machine in Segmented Outer Rotor using Appropriate Split Ratio for Electric Scooter Propulsion - Enwelum Mbadiwe I; Erwan Sulaiman; Ahmad Md Zarafi; Siti Khalidah Rahimi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Recently, permanent magnet synchronous machine (PMSM) having the diameter of 11inches was successfully developed and installed in electric scooter vehicle (ESV) for propulsion. It consists of segmented stators of 24 armature slots and 100 pieces of permanent magnet of 2 kg weight mounted on rotating rotor. Upon the huge amount of materials and permanent magnet used, PMSM produced 110Nm only. Looking at the size, this torque is low and could not sustain acceleration for long distance travels. To overcome the challenge of low torque, this paper presents a new machine type, flux switching motor (FSM) with 1 kg weight of permanent magnet flux source employing segmented outer rotor.  Six ranges of split ratio of 0.80-0.85 for outer rotor 24slot-14pole FSPM motor configurations were designed and compared. The 2D-FEA by JMAG software version 14 is used to examine its performance in term of flux linkage, cogging torque, back-emf and average torque which the structure with split ratio of 0.85 took lead by securing highest torque profile of 209Nm. It also achieved low cogging torque to operate in safe region. In conclusion, appropriate split ratio significantly enhances high torque capability of permanent magnet flux switching motor for electric scooter propulsion.